An Analysis of Syntactic Structure of Coordination on The English Translation of Surah Al-Mulk - Asridayani Asridayani; Vera Magria (Jurnal Ilmiah Langue and Parole, 2022)
This study is about Syntactic Structure of Coordination on the English Translation of Surah Al-Mulk. The purposes of this research are to find out the types of constituents to form syntactic structure of coordination on the English Translation of Surah Al-Mulk and to explain the distribution of syntactic structure of coordination on the English Translation of Surah Al-Mulk. The data is formed as sentences having syntactic structure of coordination on the English Translation of Surah Al-Mulk. Method of the research in this study is analyzed by using descriptive qualitative method. To collect the data, the writer used documentation method. The steps to analyze the data are reading, collecting, and numbering the data. To analyze the data, the writer uses structural grammar. The main theory applied in this study is the theory of Syntax proposed by Francis (1957). The result of the analysis shows that: 1) the types of constituents being combined are categorized in three groups: words which are noun, adjective, verb, and to infinitive; phrase which is noun phrase; and clauses which are independent clause and dependent clause, and 2) the distribution of syntactic structures of coordination on The English Translation of Surah Al-Mulk analyzed based on its function in word, phrase and sentence: two functions in words: as head and as modifier; one function in phrase: as modifier and one function in sentence/clause: as predicate.